Learn Unity ML-Agents – Fundamentals of Unity Machine Learning : Incorporate new powerful ML algorithms such as Deep Reinforcement Learning for games /: Incorporate new powerful ML algorithms such as Deep Reinforcement Learning for games. (2018) - Lanham, Micheal
No abstract available